EFETIVIDADE DA PRESCRIÇÃO DE CAMINHADA NÃO SUPERVISIONADA, ORIENTADA COM DIFERENTES DURAÇÕES SEMANAIS, SOBRE OS DESEMPENHOS DE MARCHA E MOBILIDADE FUNCIONAL DE INDIVÍDUOS COM ACIDENTE VASCULAR ENCEFÁLICO (AVE) CRÔNICO: UM ENSAIO CLÍNICO RANDOMIZADO - BORGES, Ronaldo Rodrigues (2021)
Introduction: Despite the motor gains after the Stroke increase with greater volumes, and the guidelines allow the recommendation of varying weekly training durations, most studies with walking intervention use 150 minutes. However, although effective, these protocols, as they require close professional supervision and / or specific equipment for the practice, are not always feasible to be taken after the end of the recovery programs. In this sense, the effectiveness of the prescription of walking training that can be obtained on the ground, in an unsupervised manner and with different weekly durations recommended for stroke, is still unknown. Objective: To compare the effectiveness of the prescription of unsupervised walking, oriented with 150 or 300 minutes per week, in the gait and functional mobility of individuals with chronic stroke. Methods: This is a randomized clinical trial in which, after clinical admission and initial tests, 40 individuals with chronic stroke received the prescription of unsupervised walking with a weekly duration of 150 (G150) or 300 minutes (G300). The period and unsupervised training was eight weeks, with evaluations at the beginning and at the end (PRE and POST). Primary variables evaluated: comfortable gait speed (CGS) using the 10-meter walk test (10MWT), the distance covered in the six-minute walk test (6MWT) and functional mobility over time in the Timed Up and Go (TUG) test; as secondary variables, the time to perform the Five Times Sit-To-Stand Test (FTSTST) and the Fast Gait Speed were evaluated, also by 10MWT. Statistics: Generalized Estimating Equations (GEE) was used to compare variables as a function of time (PRE and POST) and groups (G150 and G300) and the clinical effect size (ES) was calculated using Cohen's d; p <0.05. Results: There was no difference between the groups, being only the determining time factor for the improvement of all evaluated variables (p <0.001), resulting in a large ES for CGS, medium for Fast Gait Speed and FTSTST and small for TUG and 6MWT. Conclusion: The prescription of unsupervised walking was effective in improving the gait and functional mobility of individuals with stroke, with no difference between oriented weekly durations. Therefore, walking 150 minutes a week may be sufficient.